Metakognisi Sebagai Alat Ukur Untuk Mengetahui Kemampuan Siswa Dalam Pembelajaran Pendidikan Agama Islam - Zahiroh, Umi Khawalati (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service activity aims to identify and improve students' metacognitive abilities in Islamic Religious Education (PAI) learning. Metacognition refers to the awareness and regulation of one's own thinking processes, playing a crucial role in achieving optimal learning outcomes. The target of this activity was 30 eleventh-grade students at Pondok Pesantren Roudlotul Mubtadiin Balekambang Nalumsari Jepara. The activity was carried out through several stages: initial assessment, metacognitive education, conscious learning strategy workshop, intensive mentoring, and final evaluation. The results showed a significant improvement in students' metacognitive levels after the intervention. Initially, most students were at the tacit use level (low), but following the service program, there was a notable shift towards the aware use (moderate) and strategic use (high) levels. This activity demonstrates that strengthening metacognitive skills can be an effective solution to address the low comprehension ability of students in Islamic Religious Education subjects.